Karl Marx : a nineteenth-century life - Sperber, Jonathan (Liveright Publishing, 2013)
Between his birth in 1818 and his death sixty-five years later, Karl Marx became one of Western civilization's most influential political philosophers. Two centuries on, he is still revered as a prophet of the modern world, yet he is also blamed for the darkest atrocities of modern times. But no matter in what light he is cast, the short, but broad-shouldered, bearded Marx remains-as a human being-distorted on a Procrustean bed of political "isms," perceived through the partially distorting lens of his chief disciple, Friedrich Engels, or understood as a figure of twentieth-century totalitarian Marxist regimes. Returning Marx to the Victorian confines of the nineteenth century, Jonathan Sperber, one of the United States' leading European historians, challenges many of our misconceptions of this political firebrand turned London emigre journalist. In this deeply humanizing portrait, Marx no longer is the Olympian soothsayer, divining the dialectical imperatives of human history, but a scholar-activist whose revolutionary Weltanschauung was closer to Robespierre's than to those of twentieth-century Marxists.